Improvement and retention of emergency obstetrics and neonatal care knowledge and skills in a hospital mentorship program in Lilongwe, Malawi. Issue 2 (February 2016) - Tang, Jennifer H.; Kaliti, Charlotte; Bengtson, Angela; Hayat, Sumera; Chimala, Eveles; MacLeod, Rachel; Kaliti, Stephen; Sisya, Fanny; Mwale, Mwawi; Wilkinson, Jeffrey
Abstract: Objective: To evaluate whether a hospital-based mentoring program could significantly increase short- and longer-term emergency obstetrics and neonatal care (EmONC) knowledge and skills among health providers. Methods: In a prospective before-and-after study, 20 mentors were trained using a specially-created EmONC mentoring and training program at Bwaila Hospital in Lilongwe, Malawi. The mentors then trained an additional 114 providers as mentees in the curriculum. Mentors and mentees were asked to complete a test before initiation of the training (Pre-Test), immediately after training (Post-Test 1), and at least 6 months after training (Post-Test 2) to assess written and practical EmONC knowledge and skills. Mean scores were then compared. Results: Scores increased significantly between the Pre-Test and Post-Test 1 for both written (n = 134; difference 22.9%, P  < 0.001) and practical (n = 125; difference 29.5%, P  < 0.001) tests. Scores were still significantly higher in Post-Test 2 than in the Pre-Test for written (n = 111; difference 21.0%, P  < 0.001) and practical (n = 103; difference 29.3%, P  < 0.001) tests. Conclusion: A hospital-based mentoring program can result in both short- and longer-term improvement in EmONC knowledge and skills. Further research is required to assess whether this leads to behavioral changes that improve maternal and neonatal outcomes.